Orientação acadêmica e revisão textual : o processo de produção do trabalho de curso - (:unkn) unknown (Universidade Estadual de Goiás, 2014)
This dissertation, inserted into the field of Language and Social Practices, has the purpose of presenting a study about text revision in the context of academic advising – more specifically the advisor’s interventions in the process of End-of-course Work (EW), in undergraduation. In this research, the emphasis lies, for a matter of theme delimitation, on the teacher of Language Arts. This professional is generally considered able to carry out written textual revision works, even though he/she had not undergone any specific training and thus the advising process relies on the ability to understand and “dominate” the mother language. We seek to answer the following questions in this research: 1) Does the advisee-author show difficulties in EW composition concerning linguistic, formal and content aspects?, 2) What is the profile of activity the professor predominantly adopts along the written work advising process: advisor, revisor or co-author?, 3) How is the advising and revision process made, that is, what are the resources and the support used? After administering a questionnaire referring to the advising habits with professors from a Higher Education Institution in the state of Goiás, three advisor-professors were selected based on their preferred type of advising: a) printed, b) printed and digital and c) digital. The corpus of analysis was composed by three EW – provided by an advisee from each professor –, including its several production phases, since this research considers writing as a process, not a product. Data analysis showed that students mainly had language and form problems, so the three advisors assumed themselves predominantly as revisors of the EW they advised. For this, they resorted to the following linguistic operations: insertion, supression, addition and shift of comments, excerpts and/or words. Depending on the chosen support, the advisors could make use of comment insertions, alteration control, highlights and comments made in different colors. In the printed work, the use of these resources depends on good handwriting and organization, not to confound the student. In the digital work, these resources favor the organization of the interventions, but are more effective when previously agreed. In this sense, it was observed that the production of a EW is a complex process, which demands the guidance of a qualified reader, such as the academic advisor, and a professional revisor, since the text familiarity can impair the revision made by the own author. Besides it can expose his/her linguistic difficulties. Even if the author has great knowledge about the language and reads the same text many times, he/she will unconciously do a technical reading, which may cause the misperception of new mistakes. A “new” reading, not strictly related to the authorship and to what has been written, may detect text imperfections more effectively. It is believed, however, that this is not up to the advisor, but to the text professional.
Keywords: Revisão de texto; Orientação acadêmica; Trabalho de curso; Text revision; Academy revising; End-of-course work; CIENCIAS HUMANAS::EDUCACAO; LINGUISTICA::TEORIA E ANALISE LINGUISTICA